(untitled) (World Bulletin of Management and Law, 2023)
The market economy imposes special requirements on the specialist to participate in the development of production, to ensure high quality products with rapidly changing and technologically complex characteristics, to limit the rise in price of products by improving production methods and reducing cost. The article reveals the professional orientation of the children of the orphanage with an increase in the requirements of society for qualified specialists, the complexity and complexity of social tasks.